Papers of Christine Fernon - Fernon, Christine; Canberra Women's Liberation Group (1970)
Collection assembled by Christine Fernon relating to women's liberation movement. Comprising of the minutes from the Canberra Women's Liberation Group, notes, typescripts, photocopies, cutting books and newspaper clippings.
Manuscript reference no.: NLA MS 7689.
Christine Fernon is active in various women's groups.
Descriptive list available.
Keywords: Fernon, Christine -- Archives; Canberra Women's Liberation Group -- Archives; Feminists -- Australia -- Archives; Feminists